Pockets of hope: studies of land and people - Munzer, Martha E.; Bierhorst, John.; Conservation Foundation (New York, Alfred A. Knopf, 1967)
Studies of five economically depressed areas: Pennsylvania coal fiel ds, iron areas of upper Michigan, watersheds of Tennessee, Pueblo India n reservations of the Southwest, and underdeveloped resources of Alaska . Examines the history of land use and misuse of each region and presen ts programs for land, community, and resources development.
Includes bibliographical references: (p. 203-204)
Keywords: Natural resources -- United States -- Case studies